Źródła finansowania przedsiębiorstw przemysłowych - Żurakowska-Sawa, Joanna; Hodun, Magdalena (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2011)
This paper presented the financial sources of industrial companies. The studies included 63 companies listed on the Warsaw Stock Exchange. The period of research covered the years 2004–2009. In all branches of the analyzed companies appeared strategy of prudent financing, mainly with private capital. The difference between companies appeared in the term structure of external capital debt. Applied funding strategy could be dependent on the company’s financial situation, the strategy of action and the current financial policy objectives